Potential insulin-like and insulin-sensitizing activity on 3T3-L1 adipocytes by terpeniods isolated from Tetracera indica - Ahmed, Qamar Uddin; Hasan, Md. Mahmudul (Stu); Mat So'ad, Siti Zaiton; Bakhtiar, M. Taher; Latip, Jalifah (2017)
Aerial parts of Tetracera indica Merr. (Dilleniaceae) are traditionally used to treat diabetes in Malaysia. T. indica has been reported to contain terpenoids namely stigmasterol and betulinic acid as major constituents. Hence, the aim of this study was to evaluate in vitro antidiabetic potential of these two major terpenoids on 3T3-L1 pre-adipocytes and adipocytes. Cytotoxicity test was performed through MTT assay on 3T3-L1 pre-adipocytes to determine the safe dose for further in vitro antidiabetic evaluation. 2-NBDG glucose uptake test on mature 3T3-L1 adipocytes with the isolated terpenoids was carried out to confirm their antidiabetic effect. Insulin and rosiglitazone were taken as control and positive control, however, untreated cells with normal media (DMEM) was taken as negative control, respectively. Ethanol extract and its ethyl acetate fraction displayed the most significant antidiabetic effect on 3T3-L1 pre-adipocytes by showing their good ability to induce adipogenesis. Upon repeated silica gel column chromatography, ethyl acetate fraction afforded stigmasterol and betulinic acid whose structures were elucidated through 1H-and 13C-NMR spectroscopy. Both compounds showed significant glucose uptake activity during fluorescence glucose uptake test by 2-NBDG (fluorescent glucose analogue) on mature adipocytes by displaying higher 2-NBDG uptake than insulin at their highest concentrations. Furthermore, both terpenoids showed more or less similar 2-NBDG uptake like rosiglitazone. This clearly proves their insulin-sensitizing ability. Our study suggests strong antidiabetic potential of isolated terpenoids in terms of insulin-like and insulin-sensitizing abilities.